Communities of devotion : religious orders and society in East Central Europe, 1450-1800 - Crăciun, Maria; Fulton, Elaine, 1975- (Catholic Christendom, 1300-1700., 2011)
This collection of essays explores the complex relationship between western monasticism and lay society in east central Europe from the late medieval period to the eighteenth century. It is an important addition to current scholarship, showcasing fresh research on a subject and region on which little has been published in English. As such it will contribute to the reintegration of eastern and western European history, as well as expanding the existing parameters of scholarly discourse into late medieval and early modern religious practice and piety.